Učitelj inštrumenta/petja na razpotju družbenokulturne in akademske izobraževalne vizije - Šimunović, Natalija (Glasba v šoli in vrtcu, 2023)
Sociocultural phenomena in Slovenia and abroad raise concerns about the curriculum, educational goals, and methods of teaching an instrument or singing. Given the pace and diversity of social change, the problem areas lack a concrete systematic underpinning. On the other hand, the implementation of innovations and adjustment to the existing programmes is a daily challenge for instrument/singing teachers in overcrowded 21st-century classrooms, both in terms of content and structural modernisation of one-to-one teaching. A combination of informal approaches (Green, 2002) and a model of the potential learning outcomes of contemporary music education (Hargreaves et al., 2003) centred on self-concepts can improve the balance between music in and out of school.
Keywords: individualni pouk; informal learning; instrument/singing teacher; koncepti sebstva; model of potential outcomes of contemporary music education; neformalno učenje; one-to-one teaching; Samopodoba; self-concept; učitelj inštrumenta/petja; Učitelji glasbe